Effect of Audit Firm Characteristics on Audit Quality of Quoted Deposit Money Banks in Nigeria - Emovon, Felix Osayabor; Ogbonmwan , Evelyn Ehizogie (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2024)
This study investigates how the characteristics of audit firms are associated with audit quality in deposit money banks situated in Nigeria. The core explanatory variables employed or adopted were audit fees, audit tenure, and audit rotation on audit quality. The study adopted an ex-post factor research design. The population of the study consists of twelve (12) quoted deposit money banks on the Nigerian Exchange Group (NGX) as of 31st December, 2022, and twelve (12) banks were taken as the sample size using census sampling technique. The study period is from 2013 to 2022. The data were collected from the annual reports and accounts of the selected banks. Data collected were analyzed using descriptive and inferential statistics, and the hypotheses were tested using feasible generalized least squares regression analysis. The empirical findings revealed that audit fees and audit rotation have a positive and significant effect on audit quality, while audit tenure has a negative and significant effect on audit quality. On the basis of the findings, the study concludes that audit fees and audit rotation are important ingredients in achieving good audit quality. Establishing rotation programs with auditing should be implemented by all organizations seeking better planned undertakings of tasks regarding finance. The study recommended that banks should make use of standard audit firms like the Big 4 so as to get better audit quality, and there should be a good policy for audit rotation for the banks in order to achieve better audit quality.
Keywords: Audit Fees; Audit Quality; Audit Rotation; Audit Tenure; Nigerian Exchange Group (NGX).